Establishing the Digital Map of the Electric PowerTransmission Network (66kV) in Latakia Governorate Using Remote Sensing and Geographic Information System Techniques - حايك غسان; شاهين حسام; صارم مضر; ابراهيم معلا (Latakia University Journal -Engineering Sciences Series, 2021)
The electric power system is one of the most important infrastructure facilities that support the economic growth and development in modern societies and represents an important criterion for the development of society and the well-being of the people. The failure of this system to perform its functions causes great economic damage. Therefore, planning, designing, operating and controlling this system require the availability of effective and updated databases that enable the administrators of the system to take the appropriate decision at the right time to ensure that the system continues its work in the best way. Since this system extends over large geographical areas and has spatial dimensions, the traditional databases (non-spatial paper or computer-based databases) do not provide decision makers with the best view of the system when making their decisions. The Geographic Information System (GIS) is one of the most important spatial database systems. By integrating this system with the Global Positioning System (GPS) and the Remote Sensing system (RS), it is possible to find solutions to the problems with geographic dimension more effectively, accurately and easily. This article shows how to build the digital map of the 66kV electric power transmission network in Lattakia governorate based on the above-mentioned technologies. To establish this map, technical (electrical) data about the network was initially obtained for the study area including some paper-based maps of the mentioned network and a set of paper and electronic tables for the data of this network. Then, the GPS device was used to determine the geographical coordinates of the stations and towers of this network. Later, GIS files for stations, towers and lines were built using ArcGIS 10.3 software. Then, the digital (geographic and electrical) database for this network was built using a relational database management approach and this database was linked with the GIS files. The obtained results showed that the digital map provides great capabilities represented in solving a large number of spatial problems such as determining accurately the number and the locations of the substations and their components, the towers and the lines paths, etc., which contributes to enhance and speed up the accurate and suitable decision-making process.